Investigating the impact of varying the number of distributed energy resources on controlling the power flow within a microgrid - Fazeli, Amir; Sumner, M.; Johnson, Christopher Mark; Christopher, Edward (2015)
The electrification of heat and transport in addition to integration of intermittent renewable resources into the existing electricity network is expected to occur in near future. Such a transformation is expected to force the operation of the electricity power system at different levels to its limits and would require reinforcement of the network assets at different levels. The incorporation of active management and control within microgrids and across the low voltage distribution network is thought as a cost effective solution which would facilitate wide scale integration of the emerging distributed energy resources. However since increasing the microgrid size at a certain DER penetration level would increase the total dispatchable power it is expected to affect the effectiveness of any control algorithm that operates at that level. This paper presents the findings obtained from of an investigation into the relationship between microgrid size and the effectiveness of a deterministic control algorithm implemented at that level.